An Establishment of Long-Term Culture of Porcine Granulosa Cells and Comparison of DMEM and M199 for Cell Propagation - Youngsabanant, Mayuva; Gumlungpa, Nongnuch; Panyarachun, Busaba; Chuen-Im, Thanaporn; Panyarachun, Panadda (Thai Journal of Science and Technology, 2021)
The result disclosed that in the initiation of the granular cell culture, the cells were round-shaped, then extended and adhered to the surface of the falcon dish. As cultured for 1-2 weeks, they expanded more, and for 12 weeks, turned reticulated. After 12 weeks of culture time in M199, granulosa cells were sub-culture for compared long-term culture based on 2 formulas. The sub-cultured cells were cultured in M199 and DMEM to investigate the morphological characteristics and cell viability of granulosa cells. The result of culturing porcine granulosa cells using M199 compared to those using DMEM, exhibited that, in the beginning, both were round-shaped, and then turned sharp-headed and sharp-bottomed and stretched out. Therein, granulosa cells culture in M199 shows 39.80+4.71% of cell viability, while granulosa cells culture in DMEM shows 116.67+ 8.20% of cell viability. Based on T-test, it is revealed that cell cultures with 2 formulas were statistically significantly different (p<0.05). The advantages of this research are that it enables us to culture porcine granulosa cells efficiently by using both primary cell culture and long-term culture methods in DMEM; that we can study the morphological features, as well as the variances of the cell shapes in the laboratory; and that the cells could be utilized practically in the biotechnological field, thus assisting to economize experiment costs and eliminate animal experiments in accordance with moral norms.